A leak prevention method

TW202634016AActive Publication Date: 2026-08-16TAIWAN SELF LOCKING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
TW114104595
Authority / Receiving Office
TW · TW
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2026-08-16
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

Existing leak-proof adhesives for fasteners require high-temperature curing, which can damage metal surfaces, cause discoloration, and lead to rust or bulging, and they often crack or fall off under torque, affecting production efficiency and appearance, while traditional rubber washers increase assembly time and protrude, impacting design space.

Method used

A photocurable leak-proof material composed of 60-80% methacrylate aliphatic polyurethane oligomer, 10-34% acrylate monomer, 4-8% photoinitiator, 1-8% micronized hydrocarbon wax, and 1-4% filler, cured using UVA and UVC irradiation, forming a leak-proof layer that withstands torque and temperature without high-temperature processing.

Benefits of technology

The photocurable material achieves a leak-proof effect with good deformation, low adhesion, and low abrasion, suitable for automated production lines, maintaining appearance and safety by avoiding surface damage and ensuring reliable sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

This invention relates to a photocurable leak-proof material, a leak-proof method using the material, and its application. The photocurable leak-proof material comprises, by weight, 60% to 80% methacrylate aliphatic polyurethane oligomer, 10% to 34% acrylate monomer, 4% to 8% photoinitiator, 1% to 8% micronized hydrocarbon wax, and 1% to 4% filler. The photocurable leak-proof material of this invention can be coated onto a portion of the surface of a fastener to form a coating layer. After irradiating the coating layer with UVA and UVC light, the coating layer cures and forms a leak-proof layer. This layer is then locked onto the corresponding locking element of the fastener, resulting in a good leak-proof effect.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a light-cured leak-proof material, a leak-proof method using the light-cured leak-proof material, and its application. [Previous Technology]

[0002] In recent years, with the development of various electronic products, the need to keep the various components in electronic products dry and free from moisture or dust has been increasing. Therefore, the leak-proof function of fasteners used to assemble different components has become increasingly important.

[0003] The traditional design for leak-proof screws involves first fitting a rubber washer onto the threaded part of the screw before fastening it to the locking mechanism. The rubber washer, located between the screw seat and the locking mechanism, achieves the leak-proof purpose. This type of traditional screw requires additional time and manpower to install the rubber washer during assembly. Besides affecting production capacity and efficiency, after fastening, the screw head protrudes due to the rubber washer underneath, thus impacting design space and appearance.

[0004] Subsequently, various sectors began to replace rubber washers with anti-leakage adhesive. First, an anti-leakage adhesive layer is pre-applied to the screw seat surface, and then cured by high-temperature heating between the screw seat surface and the locking component. This allows the screw seat surface to adhere to the locking component surface, achieving the purpose of preventing leakage. However, this type of anti-leakage adhesive requires high-temperature curing. High-temperature treatment can cause discoloration and yellowing of the metal surface of the screw, and may even damage the metal plating on the screw surface, leading to rust, corrosion, or bulging. This not only affects the appearance but may also cause machine damage or reduced sealing of parts due to rust, corrosion, or bulging. The anti-leakage adhesive must withstand a certain screwing torque during fastening, and its hardness and deformation must meet the requirements for gap filling and leakage prevention. However, current commercially available products do not consider the operating temperature requirements, and the anti-leakage adhesive applied to fasteners often cracks or falls off during fastening. Furthermore, traditional leak-proof adhesives retain a slightly sticky feel after curing. When multiple screws are stacked together, slight sticking may occur between them, which is detrimental to automated feeding production lines. Overall, there is still room for improvement in commercially available leak-proof adhesives.

[0005] At present, it is still necessary to develop a leak-proof material that has good deformation under certain screwing torque conditions, while also having certain hardness, low stickiness and low roughness, and can withstand certain working temperatures. [Summary of the Invention]

[0006] In view of the aforementioned shortcomings of the prior art, one objective of the present invention is to provide a photocurable leak-proof material suitable for fasteners, wherein the leak-proof layer formed therefrom has good deformation capacity, while also possessing a certain degree of hardness, low adhesion and low abrasion, and can withstand a certain operating temperature. This photocurable leak-proof material does not require high-temperature (e.g., 130°C to 180°C) thermal curing as with traditional leak-proof adhesives; it can be coated at low temperatures and then photocured, thus avoiding damage to the metal plating on the screw surface or causing discoloration, and further improving both appearance and safety.

[0007] Another object of the present invention is to provide a leak-proof method, which can achieve a good leak-proof effect by coating the aforementioned light-curing leak-proof material onto a fastener and then performing light curing.

[0008] Another object of the present invention is to provide a leak-proof fastener, which includes a leak-proof layer formed by the aforementioned light-cured leak-proof material. In addition to achieving a good leak-proof effect, it can be applied to automated feeding production lines due to its low adhesion and low stickiness.

[0009] To achieve the above objective, the present invention provides a photocurable leak-proof material comprising: 60% to 80% by weight of methacrylate aliphatic polyurethane oligomer, 10% to 34% by weight of acrylate monomer, 4% to 8% by weight of photoinitiator, 1% to 8% by weight of micronized hydrocarbon wax and 1% to 4% by weight of filler, based on the total weight of the photocurable leak-proof material.

[0010] The present invention further provides a leak-proof method, comprising: (1) providing a fastener; (2) before fastening the fastener to its corresponding locking member, coating a portion of the surface of the fastener with a light-curing leak-proof material as described above to form a coating layer, wherein the portion of the surface of the fastener is intended to contact the locking member; and (3) simultaneously irradiating the coating layer with UVA and UVC for 3 to 60 seconds to cure the coating layer and form a leak-proof layer, thereby obtaining a leak-proof fastener, wherein the irradiation intensity of UVA is 500 milliwatts per square centimeter (mW / cm2) or more, and the irradiation intensity of UVC is 30 mW / cm2 or more; when the leak-proof fastener is fastened to its corresponding locking member, the leak-proof layer will contact the locking member.

[0011] The present invention also provides a leak-proof fastener, comprising: a fastener; and a leak-proof layer, wherein the leak-proof layer is located on a portion of the surface of the fastener and is obtained by photocuring the photocurable leak-proof material as described above. When the leak-proof fastener is fastened to its corresponding locking member, the leak-proof layer will contact the locking member.

[0012] In some specific embodiments, the methacrylate aliphatic polyurethane oligomer may be a block copolymer of α-hydro-ω-hydroxy-poly(oxy-1,4-butanediyl), 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane, and 2-hydroxyethyl methacrylate (poly(oxy-1,4-butanediyl), alpha-hydro-omega-hydroxy-, polymer with 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane, 2-hydroxyethyl methacrylate-blocked), or a copolymer or blend thereof, but is not limited thereto. In this invention, the methacrylate aliphatic polyurethane oligomer is used to provide the main structure of the leak-proof layer of this invention. In some specific embodiments, the content of the methacrylate aliphatic polyurethane oligomer, based on the total weight of the photocurable leak-proof material, may be 62% by weight, 65% by weight, 68% by weight, 70% by weight, 72% by weight, 75% by weight, or 78% by weight. More preferably, the content of the methacrylate aliphatic polyurethane oligomer, based on the total weight of the photocurable leak-proof material, is 70% to 80% by weight, or 70% to 75% by weight.

[0013] In some specific embodiments, the acrylate monomer comprises hydroxyethyl acrylate, hydroxymethyl acrylate, isobornyl acrylate, acrylicl morpholine, acrylic acid, dimethylacetoacetamide, 2-ethylhexyl acrylate, methacrylic acid, dimethylacrylamide, dimethylallylamine, or a combination thereof. In this invention, the acrylate monomer system is used to adjust the viscosity of the photocurable leak-proof material of this invention. In some specific embodiments, the content of the acrylate monomer, based on the total weight of the photocurable leak-proof material, may be 12% by weight, 15% by weight, 18% by weight, 20% by weight, 22% by weight, 25% by weight, 28% by weight, 30% by weight, 32% by weight, or 34% by weight.

[0014] In this invention, photoinitiators known in the art can be used. In some specific embodiments, the photoinitiator is an acetophenone-based photoinitiator, such as acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylamineacetophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, but not limited thereto. In this invention, the photoinitiator generates free radicals, causing the methacrylate aliphatic polyurethane oligomer to undergo a crosslinking reaction with the acrylate monomer. In some specific embodiments, the content of the photoinitiator may be 5% by weight, 6% by weight, or 7% by weight, based on the total weight of the photocurable leak-proof material.

[0015] In some specific embodiments, the micronized hydrocarbon wax is a polypropylene wax. In some specific embodiments, the polypropylene wax is a polypropylene wax with a surface carboxylate-modified structure. In some specific embodiments, the micronized hydrocarbon wax is a particulate wax with a particle size of 30 micrometers (μm) to 50 μm. In this invention, a micronized hydrocarbon wax with a relatively low specific gravity is used, for example, a micronized hydrocarbon wax with a specific gravity in the range of 0.90 g / cm3 to 1.0 g / cm3, or 0.95 g / cm3 to 0.99 g / cm3, or 0.97 g / cm3 to 0.99 g / cm3. In some specific embodiments, a micronized hydrocarbon wax with a high melting point is used, for example, a micronized hydrocarbon wax with a melting point in the range of 110°C to 190°C, or 120°C to 180°C, or 130°C to 170°C. In this invention, the micron-sized hydrocarbon wax exhibits excellent compatibility with the methacrylate aliphatic polyurethane oligomer and the acrylate monomer; it also provides a lubricating effect, reducing the friction between the fastener's seat surface and the contact surface with the locking element during fastening, controlling the seat surface friction coefficient to between 0.08 and 0.35, thereby reducing the shear force on the leak-proof layer and preventing cracking or wear; furthermore, the micron-sized hydrocarbon wax has a low specific gravity, and after coating the UV-cured leak-proof material, it floats on the surface of the UV-cured leak-proof material coating, thus forming micro-bumps after UV curing, thereby improving the slightly tacky feel of traditional leak-proof adhesives after curing. In the fastener manufacturing process, multiple fasteners may be stacked and touch each other (such as when a package contains thousands of screws). At this time, the fasteners may contact each other at various angles. The slightly tacky feel of traditional leak-proof adhesives after curing may cause the aforementioned multiple fasteners to slightly stick together, which is not conducive to the use of automated feeding production lines. In some specific embodiments, the content of the micronized hydrocarbon wax may be 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, or 7% by weight, based on the total weight of the photocurable leak-proof material.

[0016] In some specific embodiments, the filler is silica. In some specific embodiments, the silica is fumed silica. In this invention, the filler can improve the wear resistance and shear resistance of the leak-proof layer; in addition, the filler can also increase the physical cross-linking points of the photocurable leak-proof material after curing, so that when subjected to external force, the force can be dissipated in different directions, which helps to improve the mechanical strength of the cured leak-proof layer colloid and prevents cracking under certain screwing torque conditions. In some specific embodiments, the content of the filler can be 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, or 3.5% by weight, based on the total weight of the photocurable leak-proof material.

[0017] In some specific embodiments, the photocurable leak-proof material further comprises 1% to 5% by weight of additives, wherein the additives may be selected from pigments, silanes, thixotropic agents, crosslinking agents, or combinations thereof. In this invention, the addition of pigments is primarily for identification or decorative purposes. In this invention, the addition of thixotropic agents is used to reduce the flowability of the photocurable leak-proof material, aiding in shaping and preventing sagging before the photocurable leak-proof material cures. In this invention, the addition of silanes is used to reduce the surface tension of the photocurable leak-proof material after curing, thereby improving anti-sticking properties and reducing hygroscopicity. In this invention, the addition of crosslinking agents is used to enhance the curing of the photocurable leak-proof material.

[0018] In some specific embodiments, the content of the additive may be 2% by weight, 3% by weight or 4% by weight, based on the total weight of the light-cured leak-proof material.

[0019] In this invention, the photocurable leak-proof material is coated on a portion of the surface of the fastener to form a coating layer, wherein a portion of the fastener's surface will contact the locking components. In some embodiments, the fastener is a nail-shaped fastener comprising a head and a rod portion, and the photocurable leak-proof material is coated on an annular seat surface below the head of the nail-shaped body. In some embodiments, the photocurable leak-proof material is coated on at least a portion of the annular seat surface below the head of the nail-shaped body and its rod portion. In some embodiments, the photocurable leak-proof material is coated on at least a portion of the annular seat surface below the head of the nail-shaped body and its rod portion connected to the annular seat surface; that is, the leak-proof layer extends a certain height from the seat surface towards the other end of the rod portion to ensure that the area coated by the photocurable leak-proof material completely covers the main part of the fastener that contacts the locking components. In some embodiments, the nail-shaped body is a screw, a pull cap, a pop rivet, or other similar object. In this invention, the nail-shaped body (such as a screw) includes a head and a rod, and the seat surface refers to the contact surface on the bottom side of its head that contacts its corresponding locking member, and the seat surface is annular.

[0020] In some specific embodiments, step (2) includes: (2-1) heating the photocurable leak-proof material as described above at a preheating temperature to become a flowable photocurable leak-proof material; and (2-2) applying the flowable photocurable leak-proof material to a portion of the surface of the fastener before fastening the fastener to a pair of locks to form a coating layer.

[0021] In some embodiments, a pretreatment step may be further included between step (1) and step (2) to pretreat the surface of the fastener. In some embodiments, the pretreatment step is to pretreat a portion of the surface of the fastener to which the UV-cured anti-leakage material is to be coated. In this invention, the aforementioned pretreatment is used to improve the unfavorable bonding conditions on the fastener surface caused by the anti-rust treatment. In some embodiments, the aforementioned pretreatment includes applying a primer.

[0022] In some specific embodiments, the UVA irradiation intensity used in step (3) is 510 mW / cm2 or more, or 520 mW / cm2 or more. The UVC irradiation intensity is 40 mW / cm2 or more, or 50 mW / cm2 or more.

[0023] In some specific embodiments, the irradiation time of UVA and UVC used in step (3) is 3 to 60 seconds. In some specific embodiments, the irradiation time can be determined to be 3 to 60 seconds depending on the coating thickness, and it can be 3 to 10 seconds, 10 to 20 seconds, 20 to 30 seconds, 30 to 40 seconds, 40 to 50 seconds or 50 to 60 seconds.

[0024] In some specific embodiments, the preheating temperature ranges from 25°C to 40°C, or from 30°C to 35°C. In this invention, heating the photocurable leak-proof material at a preheating temperature is to avoid excessively high viscosity of the photocurable leak-proof material due to excessively low ambient temperatures (such as preparing the leak-proof fastener of this invention at around 0°C), making it difficult to flow. In this invention, the heating method for the photocurable leak-proof material can be infrared (IR) heating, hot air heating, high-frequency heating, etc., but is not limited to these methods.

[0025] In this invention, the photocuring system uses two ultraviolet light wavelengths of different wavelengths for simultaneous irradiation. These ultraviolet light wavelengths can be UVA (Ultraviolet A) and UVC (Ultraviolet C). Shorter wavelengths of ultraviolet light have higher energy, which is more conducive to rapid surface curing; while higher wavelengths of ultraviolet light have better penetration, which is more conducive to deep curing. Traditional photocuring uses an exposure wavelength of 365 nm. The photocurable leak-proof material of this invention is simultaneously exposed to two ultraviolet light wavelengths of different wavelengths, resulting in a more complete photocured leak-proof layer after complete curing.

[0026] In this invention, the wavelengths of UVA and UVC depend on the effective wavelength band of the photoinitiator. Generally, a photoinitiator has 2 to 3 suitable effective wavelength bands. After receiving light of these wavelengths, the photoinitiator will initiate the photocuring process.

[0027] In some specific embodiments, the wavelength of UVC is 220 nanometers (nm) to 280 nm, which can cure the surface of the leak-proof layer. In some specific embodiments, the absorption peak wavelength of the photoinitiator can be 230 nm to 270 nm, or 240 nm to 260 nm, or 250 nm to 260 nm.

[0028] In some specific embodiments, the wavelength of UVA is 300 nm to 400 nm, which allows for deep curing of the leak-proof layer. In some specific embodiments, the absorption peak wavelength of the photoinitiator may be 310 nm to 390 nm, or 320 nm to 380 nm, or 330 nm to 370 nm, or 340 nm to 360 nm, or 350 nm to 360 nm.

[0029] In some specific embodiments, the coating in step (2) can be performed manually or by using an artificial intelligence dispensing mechanism. In some specific embodiments, if the coating in step (2) is performed by an artificial intelligence dispensing mechanism, it can then be transported by a conveying mechanism to a UV lamp with UVA and UVC, and then photocured in step (3) to form a leak-proof layer; then it can be transported by another conveying mechanism to a screening area for automatic screening by a charge-coupled device (CCD) lens, and the preparation steps are completed on the same production line or machine.

[0030] In some specific embodiments, the thickness of the leak-proof layer is 30 μm to 200 μm. In this invention, when the thickness of the photocurable leak-proof material of this invention is increased, the light energy needs to be appropriately increased, the light power increased, or the light exposure time lengthened.

[0031] In some specific embodiments, the leak-proof layer has good leak-proof effect, reaching an IPX7 rating (it can maintain a waterproof effect for 30 minutes in water at a depth of 1 meter). In this invention, the leak-proof effect is obtained by testing according to the IEC 60529 standard.

[0032] In some specific embodiments, the Shore hardness A of the leak-proof layer is 55 to 65, or 60 to 65. In this invention, the Shore hardness A is determined according to the ASTM D2240 standard method.

[0033] In some specific embodiments, the deformation of the leak-proof layer is higher than 60%, or higher than 65%, or higher than 70%. In this invention, the deformation is determined according to the torsion test specifications of Dongri.

[0034] In some specific embodiments, the operating temperature range that the leak-proof layer can withstand is -40°C to 120°C, or -35°C to 110°C, or -30°C to 100°C, or -20°C to 90°C, or -10°C to 80°C, or 0°C to 70°C. In this invention, the term "operating temperature that the leak-proof layer can withstand" means that the leak-proof layer will not crack or fall off due to compression at this temperature. The fasteners of this invention can be applied to products that generate heat during long-term operation, such as mobile phones, tablets, computers, automotive electronic interior parts, and center console panels. These products may also be transported to colder regions, thus requiring a wide operating temperature range. In this invention, the operating temperature is determined by testing the glass transfer temperature using a differential scanning calorimeter (DSC).

[0035] In some specific embodiments, the coefficient of friction of the seat surface of the leak-proof layer is 0.08 to 0.35, or 0.1 to 0.3, or 0.15 to 0.25, or 0.15 to 0.2. In this invention, the coefficient of friction of the seat surface of the leak-proof layer is within the aforementioned range, exhibiting low friction. In this invention, the coefficient of friction of the seat surface is obtained by measuring the coefficient of friction.

[0036] In some specific embodiments, the leak-proof layer has low adhesion. In this invention, adhesion is tested using the following method: 100 screws coated with the aforementioned photocurable leak-proof material of this invention are placed in a polyethylene (PE) can with a diameter of 64 mm and a height of 120 mm, and vibrated at a frequency of 1780 cpm (cycles per minute) for 3 minutes, after which the screw adhesion ratio is calculated. In some specific embodiments, the number of screws coated with the photocurable leak-proof material of this invention that adheres after the aforementioned test is 0.

[0037] The photocurable leak-proof material of the present invention can be used to make a leak-proof layer. The photocurable leak-proof layer has good Shore hardness A, deformation and operating temperature range, and can be more widely used in electronic products such as mobile phones, tablets, computers, automotive electronic interior parts and center console panels.

Implementation Method

[0038] The object, advantages and technical features of the present invention will become apparent from the following detailed description of the embodiments and the accompanying drawings.

[0039] Preparation of the photocurable leak-proof material of the present invention

[0040] Raw Materials: 1. Aliphatic polyurethane oligomer of methacrylate: Aliphatic polyurethane oligomer of methacrylate, CAS No. 82339-26-2, is used, namely a block copolymer of α-hydro-ω-hydroxy-poly(oxy-1,4-butanediyl), alpha-hydro-omega-hydroxy-, polymer with 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane, 2-hydroxyethyl methacrylate. 2. Acrylate monomer: Isoborneol acrylate, CAS No. 5888-33-5. 3. Photoinitiator: 2,2-dimethoxy-2-phenylacetophenone, CAS No. 24650-42-8. 4. Micron-sized hydrocarbon wax: Particulate polypropylene wax with a carboxylate-modified surface, with a particle size of 30 μm to 50 μm. 5. Filler: Fumed silica (CAS No. 112945-52-5) is used.

[0041] The aforementioned raw materials were mixed at 25±3°C in the following proportions: 70% by weight of methacrylic aliphatic polyurethane oligomer, 20% by weight of acrylate monomer, 5% by weight of photoinitiator, 3% by weight of micronized hydrocarbon wax and 2% by weight of filler, to obtain the photocurable leak-proof material of the present invention.

[0042] Preparation and testing of fasteners of the present invention

[0043] First, the aforementioned photocurable leak-proof material is heated to a preheating temperature to become a flowable photocurable leak-proof material, which facilitates coating. The aforementioned preheating temperature ranges from 25°C to 40°C.

[0044] As shown in Figures 1 and 2, a screw 1 is first provided, which includes a head 10 and a shank 20. The aforementioned light-cured leak-proof material in a flowing state is coated on the annular seat surface below the head 10 and at least a portion of the shank 20 connected to the annular seat surface, with a thickness of 50 μm to 80 μm, to form a coating layer 11, thus obtaining the screw 1'.

[0045] As shown in Figure 2, the coating layer 11 is simultaneously irradiated with ultraviolet light (UVA with an irradiation intensity of 500 mW / cm2 or higher) and UVC with an irradiation intensity of 30 mW / cm2 or higher for 5 seconds, causing the coating layer 11 to begin photocuring and forming a leak-proof layer 11', resulting in a leak-proof screw 1' after photocuring treatment, which is the leak-proof fastener of the present invention. When the leak-proof screw 1' is fastened to its corresponding locking member 2, the leak-proof layer 11' will come into contact with the locking member 2.

[0046] Subsequently, relevant tests were conducted on the fasteners of the present invention:

[0047] The leak-proof effect of the leak-proof layer made of the UV-cured leak-proof material of the present invention was tested according to IEC 60529 standard. This involved attaching screws coated with the UV-cured leak-proof material of the present invention to a leak-proof fixture, placing it in an oven, heating it at different temperatures, removing it, cooling it, and then testing it. The UV-cured leak-proof layer of this invention has a more complete structure and excellent water-resistant effect, reaching an IPX7 rating (it can maintain a waterproof effect for 30 minutes in water up to 1 meter deep).

[0048] The Shore hardness A of the leak-proof layer made from the photocurable leak-proof material of the present invention was tested according to the ASTM D2240 standard method. The Shore hardness A of the photocurable leak-proof layer of this invention is below 65, which indicates good hardness. If the Shore hardness A is higher than 65, the deformation is insufficient, the compressibility is poor, and the screw head will protrude too much after fastening, causing assembly interference.

[0049] The deformation of the leak-proof layer made from the photocurable leak-proof material of the present invention was measured using a Tohnichi torque wrench according to Tohnichi's torque test specifications. It was found that when different sizes of screws (such as M8 to M4) were used for fixing with a screwing torque of 1T, the deformation of the photocurable leak-proof layer of this invention was higher than 60%, which can meet the requirements for gap filling and leak prevention. When the deformation is higher than 60%, the screw head will not cause assembly interference after tightening.

[0050] The operating temperature that the leak-proof layer made from the photocurable leak-proof material of the present invention can withstand was obtained by testing the glass transfer temperature measured using a micro differential scanning calorimeter. The operating temperature of the photocurable leak-proof layer of this invention is -40°C to 120°C, which has a good operating temperature range.

[0051] The coefficient of friction of the seat surface of the leak-proof layer made from the photocurable leak-proof material of the present invention was obtained by measuring the coefficient of friction. The coefficient of friction of the seat surface of the photocurable leak-proof layer in this case is 0.08 to 0.35, indicating that it has low friction.

[0052] The adhesiveness of the leak-proof layer made from the photocurable leak-proof material of the present invention was tested according to the following method: 100 screws coated with the photocurable leak-proof material of the present invention were placed in a 250 ml PE container (64 mm in diameter and 120 mm in height). The PE container was then fixed on a NAS vibration machine fixture and vibrated at a frequency of 1780 cpm, causing the screws coated with the photocurable leak-proof material of the present invention to collide randomly for 3 minutes. After that, the screws were poured out, and the adhesion ratio of the screws was checked and counted. The photocurable leak-proof layer of this invention has low adhesiveness and does not stick after the above test, making it suitable for use in automated feeding production lines.

[0053] As can be seen from the above, the light-cured leak-proof material of the present invention, after being cured simultaneously using two ultraviolet lights of different wavelengths, UVA and UVC, results in a leak-proof layer with a Shore hardness A of less than 65. Furthermore, according to the Dongri torque test standard, when fixed with screws of different specifications (such as M8 to M4) at a screwing torque of 1T, the deformation of the leak-proof layer is higher than 60%, preventing assembly interference. In addition, the aforementioned leak-proof layer has a seat surface friction coefficient of 0.08 to 0.35, which reduces friction between the seat surface of the fastener and the contact surface of the locking element during fastening. Its low slippage reduces the shear force on the leak-proof layer, preventing cracking or wear. Therefore, by using the light-cured leak-proof material of the present invention to create a more complete leak-proof layer on fasteners, the requirements for gap filling and leak prevention can be met. The aforementioned leak-proof layer can withstand a working temperature range of -40℃ to 120℃ and will not crack or fall off during fastening. Furthermore, the leak-proof layer made using the photocurable leak-proof material of the present invention has low adhesion, so the leak-proof fastener containing the leak-proof layer can be applied to automated feeding production lines, and has a wider range of applications. [Simplified Explanation of the Diagram]

[0054] Figure 1 is a schematic diagram of coating a fastener with the photocurable leak-proof material of the present invention to form a coating layer. Figure 2 is a schematic diagram of a fastener containing a coating layer made of the photocurable leak-proof material of the present invention being photocured to form a leak-proof layer and then fastened to a locking member.

Claims

1. A leak-proof method comprising: (1) providing a fastener; (2) before fastening the fastener to its corresponding locking member, applying a light-curing leak-proof material to a portion of the surface of the fastener to form a coating layer, wherein the portion of the surface of the fastener is intended to contact the locking member; and (3) simultaneously irradiating the coating layer with UVA and UVC for 3 to 60 seconds to cure the coating layer and form a leak-proof layer, thereby obtaining a leak-proof fastener, wherein the UVA irradiation intensity is 500 milliwatts per square centimeter (mW / cm2) or more, and the UVC irradiation intensity is 30 mW / cm2 or more; when the leak-proof fastener is fastened to its corresponding locking member, the leak-proof layer will contact the locking member; wherein... The photocurable leak-proof material comprises, by weight of the total amount of the photocurable leak-proof material, 60% to 80% methacrylate aliphatic polyurethane oligomer, 10% to 34% acrylate monomer, 4% to 8% photoinitiator, 1% to 8% micronized hydrocarbon wax and 1% to 4% filler.

2. The leak-proof method as described in claim 1, wherein the methacrylic aliphatic polyurethane oligomer is a block copolymer of α-hydro-ω-hydroxy-poly(oxy-1,4-butanediyl) with 5-isocyanate-1-(isocyanate-methyl)-1,3,3-trimethylcyclohexane and 2-hydroxyethyl methacrylate.

3. The leak-proof method as described in claim 1, wherein the acrylate monomer comprises hydroxyethyl acrylate, hydroxymethyl acrylate, isoborneol acrylate, acryloyl morpholine, acrylic acid, dimethylacetoacetamide, 2-ethylhexyl acrylate, methacrylic acid, dimethylacrylamide, dimethylallylamine, or a combination thereof.

4. The leak prevention method as described in claim 1, wherein the photoinitiator is an acetophenone-based photoinitiator.

5. The leak-proof method as described in claim 1, wherein the micron-sized hydrocarbon wax is a carboxylated modified polypropylene wax.

6. The leak-proof method as described in claim 1, wherein the filler is silicon dioxide.

7. The leak-proof method as claimed in claim 1, wherein the photocurable leak-proof material further comprises 1% to 5% by weight of an additive, and the additive may be selected from pigments, silanes, thixotropic agents, crosslinking agents or combinations thereof.

8. The leak-proof method as described in any one of claims 1 to 7, wherein step (2) comprises: (2-1) heating the photocurable leak-proof material at a preheating temperature of 25°C to 40°C to form a flowable photocurable leak-proof material; and (2-2) applying the flowable photocurable leak-proof material to a portion of the surface of the fastener before fastening the fastener to a pair of locking members to form a coating layer.